Examining Inventory Performance Measured by Days of Supply - Santhirasegaran Nadarajan; Sitraselvi Chandren; Mohd Kamarul Irwan Abdul Rahim; Kamaruddin Radzuan; Mohd.Nasrun Mohd.Nawi (International Journal of Supply Chain Management, 2018)
The aim of this conceptual paper is to examine the inventory performance focusing on days of supply. Problem focal towards the context of inventory performance further narrow down to the capability of the relevant corporate governance mechanisms in managing inventory. Basically as far as concern to corporate governance study mainly focus on financial aspects and this research explore from the angle of non-financial aspects of the inventory control thats contribute toward 60 to 70% of total manufacturing cost. Two main corporate governance variables were discussed in terms of their relative impact on inventory performance thats include CEO duality, and managerial ownership. As for inventory performance measured by the inventory perspective thats include days of supply and inventory value